GDF15 knockdown suppresses cervical cancer cell migration in vitro through the TGF‐β/Smad2/3/Snail1 pathway. Issue 12 (8th November 2020) - Li, Li; Zhang, Ruihong; Yang, Hailei; Zhang, Donghua; Liu, Jiwei; Li, Jinfang; Guo, Bin
Abstract : Growth differentiation factor 15 (GDF15), a member of the transforming growth factor β (TGF‐β) superfamily, is a prognostic biomarker of cervical cancer. In addition, GDF15 has been reported to enhance the migration of colorectal cancer cells and liver cancer stem‐like cells. However, the mechanism by which GDF15 promotes cervical cancer cell migration is not completely understood. Here, we report that GDF15 expression is enhanced in cervical cancer tissues, as well as in cultured cervical cancer cells. ShGDF15 transfection markedly inhibited expression of Vimentin, N‐cadherin and Snail1, and resulted in up‐regulation of E‐cadherin expression in HT‐3 and HeLa cells. Moreover, knockdown of GDF15 suppressed wound healing rate and reduced the number of invasive cells. Furthermore, knockdown of GDF15 significantly suppressed the expression of phosphorylated Smad2 and Smad3. The addition of TGF‐β1 partially abolished the inhibitory effects of GDF15 knockdown on the migration and invasion of cervical cancer cells. In summary, we report here that GDF15 knockdown inhibits migration and invasion of cervical cancer cells in vitro through the TGF‐β/Smad2/3/Snail1 pathway. Abstract : The expression of growth differentiation factor 15 (GDF15) is increased in cervical cancer tissues, especially in metastatic cervical cancer tissue, as well as cultivated cells. Knockdown of GDF15 markedly affects epithelial–mesenchymal transformation‐related gene expression and suppresses the migration and invasion abilities of cervical cancer cells through the transforming growth factor‐β/Smad2/3/Snail1 pathway.